ANALISIS YURIDIS KEDUDUKAN SURAT SERUAN GUBERNUR DALAM HUKUM POSITIF DI INDONESIA - Michael Graceson Loyver Sitompul; Gusliana HB; Muhammad A. Rauf (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Regional Government has the jurisdiction to legally form a regional legal product,which aims to serve as the legal basis for all activities in administering government and as aform of guaranteeing legal certainty in regulating social, national and state life.This research is normative research. This is based on library research which takesquotations from reading books, or supporting books that are related to the problem to beresearched. This research uses secondary data sources consisting of primary, secondary andtertiary book materials. This research also uses qualitative data analysis and producesdescriptive data.From the results of the research and discussions carried out, several conclusions wereobtained, namely: First, the position of the Governor's Call Letter in Positive Law inIndonesia can be said to be one of the legal products in the form of policy regulations(beleidsregel), but when referring to the provisions contained in Regulation of the Governorof DKI Jakarta No. 99 of 2021 concerning the Administration of Official Documents, in factthe position of the Governor's Call Letter is an official directive text, but with the formationof the Governor's Call Letter it is more appropriate to say that it is a policy regulation(beleidsregel). Second, the content and binding force of the Governor's Appeal Letter isbasically an appeal to the public which is persuasive in nature, however there are severalGovernor's Appeal Letters whose content and binding force do not comply with theprovisions in DKI Jakarta Governor Regulation No. 99 of 2021 concerning Procedure forOfficial Documents. Third, the arrangement of content material in the Governor's AppealLetter must be reformulated, so that in the future there is legal certainty in the ContentMaterial contained in the Governor's Appeal Letter.Keywords: Surat Seruan Gubernur - Position - Positive Law